Toward ionic-liquid-based model catalysis: Growth, orientation, conformation, and interaction mechanism of the [Tf2N]- anion in [BMIM][Tf2N] thin films on a well-ordered alumina surface - Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Paape, Natalia; Happel, Markus; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Langmuir, 2010)
Aiming at a better understanding of the interaction of ionic liquid (IL) thin films with oxide supports, we have performed a model study under ultrahigh vacuum (UHV) conditions. We apply infrared reflection absorption spectroscopy (IRAS) in combination with density functional theory (DFT). Thin films of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][Tf N] are grown on an atomically flat, well-ordered alumina film on NiAl(110) using a novel UHV-compatible evaporator. Time-resolved IRAS measured during the growth and subsequent thermal desorption points toward reversible molecular adsorption and desorption. There was no indication of decomposition. The vibrational bands are assigned with the help of DFT calculations. Strong relative intensity changes in individual [TfN] bands are observed in the monolayer region. This indicates pronounced orientation effects for the anion. The adsorption geometry of [TfN] is determined on the basis of a detailed comparison with DFT. The results suggest that [TfN] anions adopt a cis conformation in the submonolayer region. They adsorb in a slightly tilted orientation with respect to the surface, mainly interacting with the support via the sulfonyl groups. © 2010 American Chemical Society.